Benefits and Challenges of Tax Management as an Important Foundation of Corporate Financial Management - Gilbert Rely (SEAN Institute, 2023)
In the increasingly complex Business Development, tax management becomes a key element in the financial management of a company. Good tax management good tax management can be a strategic tool to improve the financial stability of the company. This study aims to identify the benefits and challenges of tax management as an important foundation in corporate financial management. This study uses a qualitative method with a descriptive approach, through literature analysis and case studies of companies that have successfully implemented tax management. The research results show that tax management plays an important role as a foundation in corporate financial management. Through effective tax management, companies can optimize tax burdens, maintain compliance with tax regulations, and increase cost efficiency. However, emerging challenges, such as rapid regulatory changes, complex tax systems, and limited trained human resources, require special attention and good mitigation strategies. Therefore, integration of tax considerations into financial planning and other business decisions is critical to avoid the risk of non-compliance and maximize tax benefits. By making tax management an integral part of corporate strategy, organizations can improve their financial performance, reduce risks, and ensure business sustainability in the face of increasingly complex market dynamics.